A method for isolating pure fungal culture - Saad, Wan Zuhainis; Sieo, Chin Chin; Ahmad, Syahida; Abdullah, Norhani; Al-Bajalany, Laith Yaseen Arif (2014)
The present invention relates to a method for isolating pure fungal culture. The method comprises of providing a sample; cutting a substantial portion of an agar prepared in a first container forming a well and a cover; lifting the cover; putting the sample to the well; enclosing the well with the cover; incubating the sample for fungal growth; cutting slantingly substantial portion of an agar prepared in a second container, using a cover slip and a forcep forming two separable upper and lower portions while retaining the cover slip on the lower portion; inserting the grown fungal onto the cover slip at the edge adjacent to the vertical wall of the agar followed by a mineral oil; enclosing the cover slip with the upper portion; and incubating the fungal to obtain a pure fungal culture. The present invention also relates to a kit for isolating pure fungal culture.